Persistence of Innate Immune Pathways in Late Stage Human Bacterial and Fungal Keratitis: Results from a Comparative Transcriptome Analysis - Chidambaram, Jaya D.; Kannambath, Shichina; Srikanthi, Palepu; Shah, Manisha; Lalitha, Prajna; Elakkiya, Shanmugam; Bauer, Julien; Prajna, Namperumalsamy V.; Holland, Martin J.; Burton, Matthew J. (Frontiers in Cellular and Infection Microbiology, 2017)
Microbial keratitis (MK) is a major cause of blindness worldwide. Despite adequate antimicrobial treatment, tissue damage can ensue. We compared the human corneal transcriptional profile in late stage MK to normal corneal tissue to identify pathways involved in pathogenesis. Total RNA from MK tissue and normal cadaver corneas was used to determine transcriptome profiles with Illumina HumanHT-12 v4 beadchips. We performed differential expression and network analysis of genes in bacterial keratitis (BK) and fungal keratitis (FK) compared with control (C) samples. Results were validated by RTqPCR for 45 genes in an independent series of 183 MK patients. For the microarray transcriptome analysis, 27 samples were used: 12 controls, 7 BK culture positive for Streptococcus pneumoniae (n=6), Pseudomonas aeruginosa (n=1), and 8 FK, culture positive for Fusarium sp. (n=5), Aspergillus sp. (n=2) or Lasiodiplodia sp. (n=1). There were 185 unique differentially expressed genes in BK, 50 in FK, and 339 common to both (i.e. genes with fold-change (FC) ≤-4 or ≥4 and false discovery rate (FDR) adjusted P <0.05). MMP9 had the highest FC in BK (91 FC, adj p=3.64 E-12) and FK (FC 64, adj. p=6.10 E-11), along with other MMPs (MMP1, MMP7, MMP10, MMP12), pro-inflammatory cytokines (IL1B, TNF) and PRRs (TLR2, TLR4). HIF1A and its induced genes were upregulated uniquely in BK. Immune/defence response and extracellular matrix terms were the most enriched Gene Ontology terms in both BK and FK. In the network analysis, chemokines were prominent for FK, and actin filament reorganization for BK. Microarray and RTqPCR results were highly correlated for the same samples tested with both assays, and with the larger RTqPCR series. In conclusion, we found a great deal of overlap in the gene expression profile of late stage BK and FK, however genes unique to fungal infection highlighted a corneal epithelial wound healing response and for bacterial infection the prominence of HIF1A-induced genes. These sets of genes may provide new targets for future research into therapeutic agents.